An investigation of the role of FAF (Female Associated Factor) in female gonad development of chickens - Oberholzer, Zane (My University, 2020)
Birds use a ZW sex determination system where males are homogametic ZZ and females are heterogametic ZW. Although it has been established that avian sex determination is governed by the inheritance of these sex chromosomes, the underlying molecular mechanism still largely remains a mystery and no gene/s have been identified as the master regulator of sex determination. The W-linked gene FAF (Female Associated Factor) is a promising candidate of ovarian development since its expression is restricted to females only and is initiated prior to the start of sex differentiation. This project aimed to determine the functional role of FAF in the gonadal development of Gallus gallus by investigating the effects of the knockdown of FAF in ZW females and the ectopic expression of FAF in ZZ males.5’-RACE was conducted on mRNA extracted from HH24-25 female whole-body and gonad tissue to annotate the 5’-UTR of FAF. Using this data, two non-overlapping morpholinos were designed to target FAF. The morpholinos and pCI-FAF-RFP expression plasmid was delivered to embryos (HH14-16) via in ovo electroporation. While male embryos electroporated with the FAF-targeting morpholinos (at 1mM and 2mM) developed to HH30-34, female embryos died 24-48 hr post-electroporation. Female embryos electroporated with the control morpholino (at 1mM and 2mM), however, developed normally to HH30-34. This suggests delivery of the construct was not isolated to the gonads alone as the gonads are not essential to survival. Consistent with this, it was identified that the morpholinos were also delivered to the dorsal aorta, suggesting FAF may have a role in the formation/functioning of the dorsal aorta. The ectopic expression of FAF in ZZ males resulted in the gonads developing a female-like morphology, suggesting a male-to-female sex reversal whereas the overexpression of FAF in ZW females had no morphological effect on the gonads. Currently it is unclear if FAF acts as a protein or non-coding RNA, however, based on the findings from this project, it is clear that FAF is implicated in normal female development and gonad differentiation which warrants further investigation
A thesis submitted in fulfilment of the requirements for the degree Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, Johannesburg, 2020